Blood pressure reduction after renal denervation in patients with or without chronic kidney disease - Günes-Altan, Merve; Schmid, Axel; Ott, Christian; Bosch, Agnes; Pietschner, Robert; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (Clinical Kidney Journal, 2024)
Background. Renal denervation (RDN) has emerged as an adjacent option for the treatment of hypertension. This analysis of the Erlanger registry aimed to compare the blood pressure (BP)-lowering effects and safety of RDN in patients with and without chronic kidney disease (CKD). Methods. In this single-center retrospective analysis, 47 patients with and 127 without CKD underwent radiofrequency-, ultrasound- or alcohol-infusion-based RDN. Office and 24-h ambulatory BP and estimated glomerular filtration rate (eGFR) were measured at baseline, and after 6 and 12 months. Results. A total of 174 patients with a mean age of 59.0 ± 10 years were followed up for 12 months. At baseline, mean eGFR was 55.8 ± 21 mL/min/1.73 m2 in patients with CKD and 87.3 ± 13 mL/min/1.73 m2 in patients without CKD. There was no significant eGFR decline in either of the groups during 12 months of follow-up. In patients without CKD, office systolic and diastolic BP were reduced by –15.3 ± 17.5/–7.9 ± 10.8 mmHg 6 months after RDN and by –16.1 ± 18.2/–7.7 ± 9.6 mmHg 12 months after RDN. In patients with CKD, office systolic and diastolic BP were reduced by –10.7 ± 24.0/–5.8 ± 13.2 mmHg 6 months after RDN and by –15.1 ± 24.9/–5.9 ± 12.9 mmHg 12 months after RDN. Accordingly, in patients without CKD, 24-h ambulatory systolic and diastolic BP were reduced by –7.2 ± 15.8/–4.9 ± 8.8 mmHg 6 months after RDN and by –9.0 ± 17.0/–6.2 ± 9.8 mmHg 12 months after RDN. In patients with CKD, 24-h systolic and diastolic BP were reduced by –7.4 ± 12.9/–4.2 ± 9.9 mmHg 6 months after RDN and by –8.0 ± 14.0/–3.6 ± 9.6 mmHg 12 months after RDN. There was no difference in the reduction of office and 24-h ambulatory BP between the two groups at any time point (all P > .2). Similar results have been found for the 6 months data. With exception of rare local adverse events, we did not observe any safety signals. Conclusion. According to our single-center experience, we observed a similar reduction in 24-h, day and night-time ambulatory BP as well as in-office BP in patients with and without CKD at any time point up to 12 months. We conclude that RDN is an effective and safe treatment option for patients with hypertension and CKD.
CRIS-Team Scopus Importer:2024-01-26
Keywords: blood pressure; chronic kidney disease; hypertension; post-hoc analysis; renal denervation